Pembentukan dan Negosiasi Identitas Digital pada Generasi Z Fatherless melalui Interaksi Simbolik di Media Sosial - Rika Yessica Rahma; Neta Agustin (Universitas Muhammadiyah Prof. DR. Hamka, 2026)
This study examines the self-concept formation process of Generation Z (aged 21–24) experiencing fatherlessness due to parental divorce, through symbolic interactionist activities on social media in DKI Jakarta. The focus on divorce-related fatherlessness was chosen because this form has a verifiable time marker across informants, while acknowledging that fatherlessness more broadly can also result from death, migration, or emotional father absence. This qualitative case study applies George Herbert Mead's Symbolic Interactionism as the primary analytical lens, complemented from the design stage by Goffman's dramaturgy and Baym's digital social validation to capture the distinct dynamics of digital self-expression. Data were collected through in-depth interviews, digital activity observation, and social media documentation from five informants in Jakarta via purposive sampling until data saturation was reached. Results indicate that informants construct their self-concept through a dialectic between the I (the spontaneous, authentic self) and the Me (the socialized self). Social media—particularly secondary Instagram accounts and X—functions as an alternative space (safe space) for expressing emotions suppressed within the domestic environment. Informants consciously engage in impression management, projecting positive images on main accounts while expressing vulnerability in more private digital spaces. Based on informants' experiences, social media plays an important role in identity negotiation and resilience-building, although these findings do not conclude that social media fully replaces the family's role.